CONTINUING EDUCATION OF TEACHERS IN EDUCATIONAL ROBOTICS: AN APPROACH WITH BASIC, INTERMEDIATE AND ADVANCED LEVELS - Mesquita, Leonardo; de Sena, Galeno José; de Lucena, Samuel Euzédice; Akamatsu, Jânio Itiro (Seven Editora, 2024)
This article aims to describe the actions of a project developed at UNESP, Guaratinguetá Campus, aimed at the training of teachers from the public school system in the region of the Education Board (DE) of Guaratinguetá. The project was developed in partnership with the DE of Guaratinguetá and included the offering of courses at three levels: basic, intermediate and advanced. In parallel with the offering of courses at the basic and intermediate levels, a board coupled to a mobile robot was developed, including several components, whose functionalities are being presented in the advanced level course. The article briefly presents the objectives of the courses offered at each level, as well as the results of the evaluations of the courses at the basic and intermediate levels. It also briefly describes the design of the mobile board/robot, the object of the advanced course. DOI:https://doi.org/10.56238/sevened2024.037-035